2015
DOI: 10.1002/cne.23833
|View full text |Cite
|
Sign up to set email alerts
|

LPXRFa peptide system in the European sea bass: A molecular and immunohistochemical approach

Abstract: Gonadotropin-inhibitory hormone (GnIH) is a neuropeptide that suppresses reproduction in birds and mammals by inhibiting GnRH and gonadotropin secretion. GnIH orthologs with a C-terminal LPXRFamide (LPXRFa) motif have been identified in teleost fish. Although recent work also suggests its role in fish reproduction, studies are scarce and controversial, and have mainly focused on cyprinids. In this work we cloned a full-length cDNA encoding an LPXRFa precursor in the European sea bass, Dicentrarchus labrax. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(120 citation statements)
references
References 97 publications
(183 reference statements)
14
105
0
Order By: Relevance
“…In sockeye salmon, goldfish GnIH (LPXRFamide peptide)-ir cell bodies are located in the nucleus posterioris periventricularis of the hypothalamus and immunoreactive fibers are distributed in the pituitary and various brain regions (Amano et al, 2006) (Table 1). Paullada-Salmerón et al (2015) developed a specific antiserum against sea bass GnIH (sbLPXRFa), which revealed sbLPXRFa-ir perikarya in the olfactory bulbs-terminal nerve, ventral telencephalon, caudal POA, dorsal mesencephalic tegmentum and rostral rhombencephalon, and sbLPXRFa-ir fibers innervate the POA, hypothalamus, optic tectum, semicircular torus and caudal midbrain tegmentum, olfactory bulbs, ventral/dorsal telencephalon, habenula, ventral thalamus, pretectum, rostral midbrain tegmentum, posterior tuberculum, reticular formation and viscerosensory lobe, retina, pineal, vascular sac, and pituitary (Table 1). In the pituitary, sbLPXRFa-ir innervation was observed close to follicle-stimulating hormone (FSH), luteinizing hormone (LH), and GH cells (Table 1).…”
Section: Encephalic Gnihmentioning
confidence: 97%
See 1 more Smart Citation
“…In sockeye salmon, goldfish GnIH (LPXRFamide peptide)-ir cell bodies are located in the nucleus posterioris periventricularis of the hypothalamus and immunoreactive fibers are distributed in the pituitary and various brain regions (Amano et al, 2006) (Table 1). Paullada-Salmerón et al (2015) developed a specific antiserum against sea bass GnIH (sbLPXRFa), which revealed sbLPXRFa-ir perikarya in the olfactory bulbs-terminal nerve, ventral telencephalon, caudal POA, dorsal mesencephalic tegmentum and rostral rhombencephalon, and sbLPXRFa-ir fibers innervate the POA, hypothalamus, optic tectum, semicircular torus and caudal midbrain tegmentum, olfactory bulbs, ventral/dorsal telencephalon, habenula, ventral thalamus, pretectum, rostral midbrain tegmentum, posterior tuberculum, reticular formation and viscerosensory lobe, retina, pineal, vascular sac, and pituitary (Table 1). In the pituitary, sbLPXRFa-ir innervation was observed close to follicle-stimulating hormone (FSH), luteinizing hormone (LH), and GH cells (Table 1).…”
Section: Encephalic Gnihmentioning
confidence: 97%
“…The grass puffer gene encodes a precursor polypeptide that may produce peptides that have C-terminal MPMRFamide or MPQRFamide sequence and one -RYamide peptide but not LPXRFamide (X = L or Q) peptides (Shahjahan et al, 2011). A polypeptide of European sea bass, which is orthologous to LPXRFamide precursor polypeptide also contains C-terminal MPMRFamide and MPQRFamide peptide sequences but not LPXRFamide (X = L or Q) peptides (Paullada-Salmerón et al, 2015).…”
Section: Structure Of Gnih Peptidesmentioning
confidence: 98%
“…On the other hand, several studies have also reported that GNIH and/or its receptor (GNIHR) are expressed in gonads [2124, 28] and are involved in the regulation of steroidogenesis in avian and mammalian species [23, 24, 26, 29]. In fish, the mechanisms of actions of Gnih on gonadotropin release and the reproductive axis are not so clear and contradictory findings have been reported [16, 18, 19, 45, 61, 62]. In addition, Gnih functions and implications in steroidogenesis and gametogenesis in teleosts have not been sufficiently assessed.…”
Section: Discussionmentioning
confidence: 99%
“…This species has also represented an interesting fish model for the study of environmental and endocrine control of reproduction [18, 3445]. Recently, we identified a gnih gene in sea bass encoding a prepro- gnih mRNA that gives rise to two different RFamide peptides, named as sbGnih-1 and sbGnih-2, which are produced by proteolytic processing from a single protein precursor [45]. In a previous study [18], we reported an inhibitory role of Gnih (mainly sbGnih-2) in the reproductive axis of sea bass by acting at the brain and pituitary level.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GnIH and its homologous peptide inhibit the release of gonadotropin in higher vertebrates. In a search for novel factors regulating reproduction of fish using the D. labrax as a model [22], Paullada-Salmerón and colleagues isolated a GnIH ortholog precursor containing two putative GnIH peptides (sbGnIH-1 and sbGnIH-2). However, studies in fish have shown both stimulatory and inhibitory roles of GnIH in the reproductive axis by using pituitary cultures and intraperitoneal injection.…”
mentioning
confidence: 99%